1981
DOI: 10.1159/000237993
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Moxalactam with Emphasis on Infections Due to Multidrug-Resistant Organisms in Patients with Renal Insufficiency

Abstract: The efficacy of moxalactam, a new beta-lactam antibiotic with an expanded spectrum of in vitro activity, was evaluated in 22 patients with 27 sites of infection. The pathogens included six strains of multidrug-resistant Serratia marcescens and one of Pseudomonas aeruginosa. The minimal inhibitory concentration of moxalactam for the study isolates ranged from less than 0.12 to 32 μg/ml. Peak serum levels exceeded the minimal inhibitory concentration of the pathogen in every instance with mean peak serum levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
1985
1985

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Many were optimistic that this relatively safe drug might prove useful as a single agent for infections previously requiring aminoglycoside therapy. Early clinical trials showed moxalactam to be safe and effective for a wide spectrum of bacterial infections (3,(19)(20)(21) with a final volume of 3 ml and a final inoculum of 105 colony-forming units (CFU) per ml. The minimal inhibitory concentration (MIC) was defined as the lowest antibiotic concentration preventing macroscopically detectable growth after 18 h of incubation at 35°C in air.…”
mentioning
confidence: 99%
“…Many were optimistic that this relatively safe drug might prove useful as a single agent for infections previously requiring aminoglycoside therapy. Early clinical trials showed moxalactam to be safe and effective for a wide spectrum of bacterial infections (3,(19)(20)(21) with a final volume of 3 ml and a final inoculum of 105 colony-forming units (CFU) per ml. The minimal inhibitory concentration (MIC) was defined as the lowest antibiotic concentration preventing macroscopically detectable growth after 18 h of incubation at 35°C in air.…”
mentioning
confidence: 99%
“…The poor drainage associated with bronchial obstruction added to the difficulty in treatment, but the susceptibility to ceftriaxone decreased eightfold while the patient was on therapy (Table 1). Although not studied in this patient, selection of resistant organisms from an original heterosusceptible population has been described in similar situations with other new 3-lactam antibiotics (8,15). …”
Section: Resultsmentioning
confidence: 73%